Preface - Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science; Vol 24 No 2 (2017), 2017)
We present the next issue of CAMES in which you will find four articles addresing various computational aspects in the development of classification algorithms in inverse problems as well as in modeling of delamination in composites. CAMES has been published since 2012 under the auspices of European Community on Computational Methods in Applied Sciences (ECCOMAS). This patronage is both a challenge and a commitment for our Journal to ensure the highest scientific publications’ standards. Back in 2012, it was decided that the Advisory Editorial Board of CAMES consists of representatives of the Managing Board of ECCOMMAS. The composition of that Managing Board has changed since then. Therefore, we are updating the membership list of our Advisory Board. Furthermore, we are adding to it the ECCOMMAS Technical Committes’ Chairmen.